Pre-service teachers’ inquisitiveness in mathematics learning - Umah, Ulumul; Rahmawati, Ana (Pusat Studi Pengembangan Pembelajaran Matematika, 2023)
Inquisitiveness is a critical thinking disposition that is important in the inquiry process because it relates to the tendency to ask questions. However, studies on inquisitiveness in the domain of mathematics learning are still limited. Several previous studies have only explained inquisitiveness based on general attitudes without involving the context of the field of mathematics. This study aims to describe the inquisitiveness of mathematics prospective teacher students which is showed in asking questions. This research is a qualitative research with prospective teacher students at Universitas Pesantren Tinggi Darul Ulum as the participants. The research data was collected through tests, observations, and interviews. The results of the study show that the tendency of prospective mathematics teacher students to ask effective questions when responding to information in mathematical problems is still low. Prospective teachers cannot always ask questions even if they do not understand the rationale behind a statement. Another finding from this study is that even though prospective teachers can ask questions in discussion, their questions cannot meet the inquisitiveness criteria because they are less successful in developing in-depth understanding.